Evaluating the accuracy between hollow and solid dental aligner models: a comparative study of printing technologies - Yurdakurban Ebru; Topsakal Kübra Gülnur; Duran Gökhan Serhat; Görgülü Serkan (Sciendo, 2024)
To evaluate the accuracy between hollow and solid dental models produced using a StereoLithography Apparatus (SLA), Digital Light Processing (DLP), and PolyJet 3D printing technologies.